Effects of acute aerobic exercise on brain-derived neurotrophic factor level in rheumatoid arthritis patients - Yentur, Songul Baglan; Ercan, Zubeyde; Deniz, Gulnihal; Karatas, Ahmet; Gur, Mustafa; Alkan, Gokhan; Koca, Suleyman Serdar (Turkish League Against Rheumatism, 2023)
Objectives:The study aimed to investigate the variation of brain-derived neurotrophic factor (BDNF) levels following acute exercise in patients with rheumatoid arthritis (RA). Patients and methods: This cross-sectional study was conducted with 88 participants (25 males, 63 females; mean age: 45.1 & PLUSMN;8.3 years; range, 18 to 65 years) between July 2020 and May 2021. Of the participants, 44 were RA patients, and 44 were age-and sex-matched healthy controls. Aerobic exercise was utilized in all participants for a single session. Depression and anxiety levels were evaluated with the Beck Depression Inventory and Hospital Anxiety and Depression Scale. Blood samples were collected from all subjects before and immediately after the intervention. Results: Serum BDNF levels (both baseline and after exercise) were similar in the RA and control groups. Although serum BDNF levels significantly decreased in both groups after aerobic exercise (Wilcoxon rank p<0.05), & UDelta;BDNF levels were significantly higher in the RA group than in the control group (p=0.047). Additionally, & UDelta;BDNF levels were significantly correlated with the Hospital Anxiety and Depression Scale scores in the RA group (p<0.05) but not in the control group. Conclusion: A single bout of exercise may effectively decrease serum BDNF levels in patients with RA and healthy subjects. The long-term effect of exercise on BDNF levels should be investigated in prospective studies.
Keywords: Brain-derived neurotrophic factor; rheumatoid arthritis; physical exercise